Estimating Returns to Schooling and Experience: A History of Thought - Barry R. Chiswick (Institute of Labor Economics (IZA), 2023)
This paper is a review of the literature in economics up to the early 1980s on the issue of estimating the earnings return to schooling and labor market experience. It begins with a presentation of Adam Smith's (1776) analysis of wage determination, with the second of his five points on compensating wage differentials being "the easiness or cheapness, or the difficulty and expense" of acquiring skills. It then proceeds to the analysis by Walsh (1935) estimating the net present value of investments at various levels of educational attainment. Friedman and Kuznets (1945) also used the net present value method to study the earnings in five independent professional practices. Based on the net present value technique, Becker (1964) estimates internal rates of return from high school and college/university schooling, primarily for native-born white men, but also for other demographic groups. The first regression-based approach is the development of the schooling-earnings function by Becker and Chiswick (1966), which relates the logarithm of earnings, as a linear function of years invested in human capital, with the application to years of schooling. This was expanded by Mincer (1974) to the "human capital earnings function" (HCEF), which added years of post-school labor market experience. Attractive features of the HCEF are discussed. Extensions of the HCEF in the 1970s and early 1980s account for interrupted labor marker experience, geographic mobility, and self-employment and unpaid family workers.
Keywords: I24; I26; J3; J46; J61; O15; B29; 330; human capital; schooling earnings function; human capital earnings function; schooling; labor market experience; women; immigrants; less developed countries; self-employed; unpaid workers